Magnetic Susceptibility of Soil to Differentiate Soil Environments in Southern Brazil - Ramos, Priscila Vogelei; Diniz Dalmolin, Ricardo Simao; Marques Junior, Jose [UNESP]; Siqueira, Diego Silva [UNESP]; Almeida, Jaime Antonio de; Moura-Bueno, Jean Michel (Soc Brasileira De Ciencia Do Solo, 2017)
The interest in new techniques to support digital soil mapping (DSM) is increasing. Numerous studies pointed out that the measure of magnetic susceptibility (MS) can be extremely useful in the identification of properties related with factors and processes of soil formation, applied to soil mapping. This study addressed the effectiveness of magnetic soil susceptibility to identify and facilitate the distinction of different pedogenic environments of a representative hillslope in the highland Planalto Medio in the state of Rio Grande do Sul (RS), Brazil. In a 350-ha area in the municipality of Santo Augusto, RS, a representative transect was selected, trenches opened for soil characterization and 29 grid points marked at regular distances of 50 m, where soil samples were collected (layers 0.00-0.05, 0.05-0.15, 0.15-0.30, and 0.30-0.60 m) to analyze soil properties. Data from the transect samples were subjected to descriptive statistics. Limits of the pedogenetic environments along the slope were identified by the Split Moving Window (SMW) Boundary Analysis. The combined use of soil magnetic susceptibility and the SMW technique was effective in identifying different pedogenetic environments in the study area.
Keywords: pedometrics; geomorphology; detailed mapping